Strategic human resource management, leadership, and governance practices in a university hospital: a qualitative study of healthcare managers’ experiences - Nuriye Sarıakçalı (Hitit Sosyal Bilimler Dergisi, 2026)
Strategic human resource management, leadership, and governance are recognized as complementary management processes that play a fundamental role in enhancing organizational effectiveness and improving the quality of healthcare services. However, translating these processes into practice is often challenged by competing organizational priorities, structural constraints, and limited resources. This qualitative study, drawing on the experiences of physicians, nurses, and administrative managers working in a public university hospital, aims to examine how strategic human resource management and leadership practices are carried out, how these practices reflect in employee engagement and performance, the main challenges encountered during implementation, and how misalignments between policy and everyday practice are managed. Additionally, managerial strategies developed to support motivation and sustainable performance are interpreted through a qualitative lens. Data were collected through semi-structured, in-depth interviews with purposively sampled managers, and the data were analyzed using Braun and Clarke’s thematic analysis approach. The study's reporting aligned with COREQ guidelines developed for qualitative interview research. The analysis identified six interrelated themes: (i) competency-based planning, training and development, and quality-oriented strategic HRM practices; (ii) relational leadership, role modeling, and trust building; (iii) fairness, transparency, and accountability in governance processes, along with policy-practice misalignments; (iv) staff shortages, increasing workload, and the risk of burnout; (v) managerial strategies supporting motivation and employee engagement; and (vi) local adaptation and innovative solution practices developed under structural constraints. The findings indicate that balancing institutional performance targets with workforce capacity cannot be achieved solely through technical planning tools; rather, the sustainability of this balance depends critically on fair and transparent governance mechanisms that are perceived as legitimate by frontline staff. The study contributes qualitative evidence to ongoing discussions on the integrated consideration of strategic HRM, leadership, and governance processes and aims to offer analytical insights to inform policy development and institutional improvement efforts in healthcare organizations.